The rise of digital advertising in eSports: A case study on Twitch - Singh, Ashmita (The IIE, 2022)
According to Edery and Mollick (2008), the increasing effectivity of human connection through digital interaction, trending entertainment and advertising being combined has greatly benefitted brands which have integrated such combinations into their digital advertising. Therefore, this study explores the benefits and value of the rise of digital advertising on Twitch in eSports content as the current digital shift has been of great power for brands towards enhancing brand equity through innovative digital advertising. This research also aims to explore how brands utilise innovativeness and creativity in digital advertising within Twitch with eSports content to increase and enhance brand equity. Twitch is deemed to be an impactful livestreaming platform which integrates advanced technology, live entertainment, real-time interaction, and competitive online gaming (Carter and Egliston, 2018). Thus, expanding the horizon for brands to increase creativity and innovation within advertising by integrating growing platforms and trends as such to increase brand equity, grow consumer markets and support eSports teams and players. Due to offline games being restrictive of real-time interaction with brands’ advertisements and overall internet access, the advertisements within offline gaming had lacked impactful creativity and measurable impact, which is counteracted by eSports through eSports being online, in real-time and with live interaction between players, teams and audiences when streamed on platforms such as Twitch. This research proposal consists of the interpretivism paradigm with a qualitative approach and methodology within which a questionnaire was formulated to obtain insight into the experiences, opinions and perceptions of Generation Z gamers who utilise Twitch for eSports. This paradigm and methodological approach were undertaken to understand and explore the value in innovative brand advertising on Twitch in eSports, the growth of brands and enhancement of brand equity thereof. Findings derived depicted that an extensive amount of value is added to brands exploring new technological platforms, such as Twitch, sponsorships, and interactive advertisements as well as the effectivity of brand partnerships with endorsements. This successfully contributed to the research aim and question as findings support the notion that brand advertising on Twitch in eSports content provides value to the growth of brands and enhancement of brand equity. Findings also included respondents deeming adverts on Twitch in eSports to be more interactive and effective in engagement whereas offline videogames restricted the reach of brands in the interactive aspect and enabling audiences to be able learn more in real time with effective engagement. This research’s key contribution aims towards understanding how brands digital advertising opportunities on Twitch in eSports enhance brand equity, resonance and shape perceptions of consumer markets. This research findings also contribute towards how digital brand advertisements have a significant impact on shaping consumer perceptions on Twitch during live streams of eSports and persuasion to learn more about brands, understand the value communicated and build meaningful brand relationships which in turn enhances brand equity.
Keywords: Digital marketing; Brand communication; Video games; Creative advertising; Brand awareness